Alcohol health warning labels: a rapid review with action recommendations - Giesbrecht, Norman; Reisdorfer, Emilene; Rios, Isabelle (My University, 2022)
A rapid review of research on health warning labels located on alcohol containers (AWLs) was conducted. Using five search engines (Embase, Medline, Pubmed, Scopus, Psyinfo), 2975 nonduplicate citations were identified between the inception date of the search engine and April 2021. Of those, 382 articles were examined and retrieved. We selected 122 research papers for analysis and narrative information extraction, focusing on population foci, study design, and main outcomes. Research included public opinion studies, surveys of post-AWL implementation, on-line and in-person experiments and real-world quasi-experiments. Many studies focused on the effects of the 1989 United States Alcoholic Beverage Labeling Act on perceptions, intentions and behavior. Others focused on Australia, Canada, the United Kingdom, England or Scotland, Italy and France. There was substantial variation in the design of the studies, ranging from small-scale focus groups to on-line surveys with large samples. Over time, evidence has been emerging on label design components, such as large size, combination of text and image, and specific health messaging, that is likely to have some desired impact on knowledge, awareness of risk and even the drinking behavior of those who see the AWLs. This body of evidence provides guidance to policy-makers, and national and regional authorities, and recommendations are offered for discussion and consideration.
Keywords: alcohol; health warning labels; knowledge; awareness; behavior; pregnancy; cancer; design; message; policy recommendations